Peran Kepemimpinan dan Keyakinan Diri Wirausaha dalam Meningkatkan Ketahanan Bisnis UMKM di DKI Jakarta - Anwar, Nabila Talitha; Hayati, Keumala (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: To determine whether the independent variables (entrepreneurial leadership and entrepreneurial self-efficacy) have a positive and significant effect on the dependent variable (business resilience) in MSMEs in DKI Jakarta. Methodology/approach: This research methodology adopts a quantitative approach because it provides greater objectivity in conducting research, thereby reducing personal interpretation and allowing for a more structured analysis. Purposive sampling was used because it allows for the selection of respondents who are more specific and relevant to the required research. Results/findings: The findings support the proposed hypotheses, indicating that both entrepreneurial leadership and entrepreneurial self-efficacy have a significant positive effect on business resilience where p-value < 0,05 and t-calculated > t-table on both independent variables. Conclusion: Entrepreneurial leadership and self-efficacy play important roles in enhancing the business resilience of MSMEs in Jakarta. Developing leadership skills and self-confidence through training and mentoring can help MSMEs become more resilient, adaptive, and sustainable. Limitations: The limitations of this study include the expansion of the research location, the need to improve entrepreneurial leadership and self-efficacy, and the strengthening of MSME business resilience. Contribution: This study is expected to contribute to a deeper understanding of the relationship between entrepreneurial leadership and entrepreneurial self-efficacy as key factors influencing business resilience in future research.